(untitled) (Agricultural Engineering, 2020)
The paper discusses supplier evaluation as a tool for controlling the level of service in a production enterprise based on data from the selected production company. The suppliers were assessed and analyzed based on their respective assortment groups and strengths and weaknesses of their activity were indicated. It was found that the supply chain in the analyzed company is largely determined by the type of ordered goods, the place of its production and the method of its distribution to the customer.